2019
DOI: 10.1021/acs.joc.9b01557
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Synthesis of 2,3-Dihydrobenzofurans via a Formal [4+1] Annulation of Propargylamines with Sulfur Ylides

Abstract: A simple, general route to the 2,3-dihydrobenzofurans substituted at C3 by an aryethynyl or aryl group, starting from propargylamine and its derivatives with benzoyl sulfonium salts, has been developed. This reaction involved an in situ generated o-quinone methide (o-QM) intermediate followed by [4+1] annulation with sulfur ylides. Notably, this protocol's features include moderate to excellent yields and remarkable diastereoselectivity (>20:1 dr in general), easy performance, as well as applicability to vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…49 Another approach to generate quinoid intermediates is the thermolysis of Mannich bases. Thus, He et al 50 showed that phenols 54 produce dihydrobenzofurans 55 upon heating with sulfonium salts 10 in aqueous acetonitrile (Scheme 22). In this case, the piperidine molecule served as a leaving group and also as a base, which generated sulfonium ylides from the corresponding salts 10.…”
Section: [4 + 1]-annulations With Sulfur Ylidesmentioning
confidence: 99%
“…49 Another approach to generate quinoid intermediates is the thermolysis of Mannich bases. Thus, He et al 50 showed that phenols 54 produce dihydrobenzofurans 55 upon heating with sulfonium salts 10 in aqueous acetonitrile (Scheme 22). In this case, the piperidine molecule served as a leaving group and also as a base, which generated sulfonium ylides from the corresponding salts 10.…”
Section: [4 + 1]-annulations With Sulfur Ylidesmentioning
confidence: 99%
“…[9] More recently, the Shang group described an efficient and simple synthesis of dihydrobenzofurans by employing propargylamines and benzoyl sulfur salts under catalyst-free conditions (Scheme 1a, Eq 4). [10] Those protocols enriched the synthetic routes of 2,3-dihydrofuran derivatives. Nevertheless, their applications were limited by poor enantioselectivity, toxic solvents and high reaction temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Directing group-assisted catalytic C–H bond functionalization and annulation has attracted much attention due to the feasibility and step economy for access to diverse cyclic heteroarenes, which are ubiquitous in many pharmaceuticals, natural products, and functional materials . Due to our long-standing research interest in the construction of privileged heterocycles, we envisioned that the transformable methylphenyl sulfoximine (MPS) could promote transition metal-catalyzed carbenoid insertion and annulation reactions and open a novel avenue to challenging heterocycles. We herein developed the first Rh-catalyzed continuous double carbenoid insertion and diannulation reaction (Scheme f).…”
mentioning
confidence: 97%